"Dragon boating" alone? Community ties and systemic income shocks. (28th October 2021) - Matakos, Konstantinos; Minos, Dimitrios; Perdana, Ari; Radin, Elizabeth
Abstract: Can social capital effectively cushion households against adverse income shocks, especially in the absence of formal insurance mechanisms in developing countries? And what if such shocks are due international finance and thus universal and systemic in nature? We analyse whether participation in formal and informal community activities (our measure of social capital) helped households in Indonesia mitigating the impact of the 1998 financial crisis. We use the 1997 and 2000 rounds of the Indonesian Family Life Survey (IFLS) to capture the impact of the crisis on household welfare and assess the potency of social capital as a safety net. In contrast to previous studies, our empirical results do not lend support to this hypothesis. Using a fuzzy regression discontinuity design (RDD)—coupled by an IV strategy for extrapolation, we find community participation not to be statistically significant in explaining changes in household expenditure. The large magnitude and universal nature of the shock might explain why social capital did not help households. However, we find some suggestive evidence that households who participated in such activities are more likely to have received financial assistance from the local community without necessarily being the neediest ones.